Effect of Ozone Treatment on The Quality and Shelf Life of Spiced Fish Floss Using Arrhenius-Based Accelerated Shelf-Life Testing - Puan Mutia Ayunisa; Dewi Sartika; Gusri Akhyar Ibrahim; Sri Hidayati; Sussi Astuti (Universitas Airlangga, 2026)
Spiced fish floss is a nutritious and practical food product combining animal protein with local spices. However, information regarding its quality changes and shelf life remains limited. This study aimed to evaluate the effect of ozone treatment on the quality and shelf life of spiced fish floss during accelerated storage. An experimental study with two replications was conducted using two treatments: ozone treatment and no ozone treatment. The products were packed in aluminium foil and stored at 30°C, 40°C, and 50°C for 28 days. Quality evaluations were conducted on days 0, 7, 14, 21, and 28 by measuring moisture content, free fatty acid content, total plate count, and sensory attributes. Shelf life was estimated using Arrhenius-based Accelerated Shelf-Life Testing, with calculations performed in Microsoft Excel 2021. The results showed that spiced fish floss without ozone treatment had the longest estimated shelf life, reaching 206.31 days at 30°C. In contrast, ozone-treated products showed a shorter estimated shelf life of 205.33 days at the same temperature. Ozone treatment was associated with increased lipid oxidation and faster quality deterioration, particularly in this high-fat product. Therefore, spiced fish floss without ozone treatment demonstrated better quality stability and a longer estimated shelf life than ozone-treated products.